2020
DOI: 10.1158/1078-0432.ccr-19-3018
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule Engagement with Taxane Is Altered in Taxane-Resistant Gastric Cancer

Abstract: Conflicts of Interest disclosure statement M.A. Shah reports receiving commercial support from Gilead Sciences, Merck, Boston Biomedical, Oncolys BioPharma, Bristol-Myers Squibb and is a consultant /advisory board member for Astellas Pharma and Lilly Japan. The other authors declare no potential conflicts of interest.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…Mechanisms of resistance to cytotoxic therapy are multifactorial and are likely to include both tumor-intrinsic genomic alterations and aspects of the tumor microenvironment. We have previously demonstrated that microtubule engagement within the tumor is an important prerequisite for taxane efficacy (27). Here, our data suggest that both HER2 amplification/overexpression and enrichment of M2 macrophages in the tumor immune microenvironment may also play a role in taxane sensitivity.…”
Section: Cabazitaxel In Gastricsupporting
confidence: 54%
See 1 more Smart Citation
“…Mechanisms of resistance to cytotoxic therapy are multifactorial and are likely to include both tumor-intrinsic genomic alterations and aspects of the tumor microenvironment. We have previously demonstrated that microtubule engagement within the tumor is an important prerequisite for taxane efficacy (27). Here, our data suggest that both HER2 amplification/overexpression and enrichment of M2 macrophages in the tumor immune microenvironment may also play a role in taxane sensitivity.…”
Section: Cabazitaxel In Gastricsupporting
confidence: 54%
“…We have previously demonstrated that microtubule bundling identified on on-treatment biopsies is associated with response to therapy (27). The underlying purpose of the correlative studies in this report was to identify any potential association of genetic aberrations or tumor microenvironment signatures with cabazitaxel activity.…”
Section: Correlative Studiesmentioning
confidence: 89%
“…Several studies have debated the possible correlation between taxane resistance and high ßIII-tubulin expression. Expression of the neuron-specific βIII-tubulin isotype correlated with taxane resistance in vitro and in vivo and has been extensively studied as a clinical biomarker of taxane efficacy [17]. Our study revealed that βIII-tubulin is frequently overexpressed in mammary gland carcinoma after PTX and DOX treatment.…”
Section: Discussionmentioning
confidence: 68%
“…China has a high GC incidence and a heavy disease burden, with an estimated 320,000 annual deaths, accounting for 45% of all GC deaths globally [ 2 ]. Despite the constant iterations of comprehensive therapy based on surgical resection, GC prognosis remains poor, with a 5-year survival rate of not more than 30% [ 3 ]. On one hand, this is attributed to the malignant phenotype of the tumor; while on the other hand, the tumor microenvironment plays an essential role as an “accomplice” [ 4 ].…”
Section: Introductionmentioning
confidence: 99%